(untitled) (SIRJANĀ – A Journal Of Arts and Art Education, 2016)
It all began with the relevant documents on caryāgīti indentified by Hara Prasad Shastri in possession of Darbar Library of Kathmandu in 1907 A.D. Just after that, a modern academic study of caryāgīti started taking its shape with the publication of the document in Calcutta in 1916, exactly hundred years back from today. Subsequent editions followed in 1951 and 1959. The book was written in Bengali and was titled in Bengali which meant ‘Hundred years old Bauddha Gāna O Dohā written in Bengali’ though it became popular as ‘Bauddha Gāna O Dohā’. It had four parts: First part was titled ‘caryācaryaviniścaya’, the second was ‘Dohākoşa’ of Saraha or Saroruhavajra, the third was ‘Dohākoşa’ of Kaņhā or Kŗşņacaryapada and the fourth was Đārkarņavā Tantra.